Effectiveness and Safety of Dose-Specific DOACs in Patients With Atrial Fibrillation: A Systematic Review and Network Meta-Analysis - Sang-Hyeon Oh; Seunghyun Cheon; Seo-Yong Choi; Young Seo Kim; Han-Gon Choi; Jee-Eun Chung (Cardiovascular Therapeutics)
Conclusions: This study found that all DOACs provided comparable or superior effectiveness and safety to warfarin. SD apixaban, SD edoxaban, and LD edoxaban achieved a favorable balance between preventing S/SE and MB risk.